Pengembangan Budaya Baca dalam Dunia Pendidikan di MTs Ma’arif Al Ishlah Bungkal Ponorogo - Purnomo, Edy (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Reading is the most important aspect in the education world. The reading culture planting among students has an important role for the information society. The purpose of this paper is to describes reading culture and reading culture development toward education. This paper uses descriptive qualitative research. The techniques used is criterion- based sampling technique. The method of data collection is scrutinized method. The results of this study is there are lower interest in reading as an indicator of the lack of habitual reading in Indonesian society. The efforts made by schools to develop a reading culture in education are 1) Propaganda Reading, 2) Sanctions Reading, 3) Changes in Behaviour, 4) Modelling, 5) Provision of Special Time for Reading Routine, 6) Parental Involvement Student, 7) Management and Development Library, 8) Environmental Restructuring Schools and classes and 9) Establishment of Reading Club.